Drugs in development for herpes simplex and varicella zoster virus. Issue 1 (17th March 2017) - Birkmann, A; Zimmermann, H
Abstract : The alpha‐herpesviruses varicella zoster virus (VZV) and herpes simplex virus (HSV) share common features including lifelong persistence in sensory ganglia and the risk of recurrences. For both HSV and VZV, standard‐of‐care (SoC) is based on nucleoside analogs (NAs), which require specific activation in infected cells. These existing drugs exhibit substantial limitations, warranting the development of new and more effective drugs.